Optimizing creep lifetime of friction stir welded PMMA pipes subjected to combined loadings using rheological model. (October 2019) - Vakili-Tahami, Farid; Adibeig, Mohammad Reza; Hassanifard, Soran
Abstract: The most important feature of the polymeric pipes is that they creep even at room temperature. Therefore, investigating the creep behavior of the polymers and their welded joints is a major concern in the mechanical engineering. The aim of this research is to estimate the creep lifetime of the friction stir welded Polymethyl Methacrylate (PMMA) pipes which operate under combined loading. To develop the creep constitutive equations for both weld zone and parent material, creep test samples have been cut from the weld zone and parent material of a PMMA sheet with friction stir butt welded joint. Constant load tests have been carried out at different initial stress and temperature levels. Based on the results of the tests, parameters of the modified Burgers model form of the constitutive equation have been derived. To validate the model, it is introduced to finite element software "ABAQUS" and the simulated creep behavior is compared with the experimental data. Furthermore, the developed constitutive model and the reference stress method (RSM) are used to produce a set of graphs which provide optimum creep lifetime and design conditions for the friction stir welded PMMA pipes that are subjected to combined internal pressure and rotation. The results show that despite using optimum conditions, creep life of the welded pipes is significantly lower than the non-welded pipe. Highlights: Friction stir welding process is performed on PMMA sheet to produce polymeric butt welded joint. Uniaxial creep tests have been carried out on parent material, weld material and butt welded joint under different temperature. The modified Burgers model has been employed to model the creep behavior of butt welded joint. The creep lifetime of specimns has been studied based on rheological model and compared with the experimental data. A set of diagrams has been proposed to estimate the optimum creep lifetime of a welded pipe which is subjected to combined loadings.